Stock Index Futures Hedging and the Impact of the 2008 Global Financial Crisis : Empirical Evidence from Five Asian Markets - Elias, George (2013)
This empirical study examines the hedging effectiveness of stock index futures for five emerging futures markets in Hong Kong, Singapore, Malaysia, Taiwan and Thailand. The hedging effectiveness is examined with respect to the impact of the recent 2008 financial crisis. Several hedging strategies to estimate hedge ratios (MVHRs) have been proposed in the literature. While these strategies hold theoretical appeal, there is no clear evidence as to their effectiveness in reducing the market risk. Using daily time series data from January 1st, 2004 to April 26th, 2012 for all the indices futures markets (except for Thailand, from April 28th, 2006 to April 26th, 2012); this study uses four different hedging strategies to estimate the MVHRs. Specifically, the conventional OLS model, Bivariate Vector Autoregression model (Bivariate-VAR), Vector Error Correction Model (VECM) and the Bivariate-GARCH model with cointegration are employed. Then the hedging effectiveness is measured based on the risk-return and the minimum variance framework. The empirical results indicate the following; firstly, the MVHRs estimated from the Bivariate-GARCH are slightly relatively superior. Secondly, during the crisis period, the MVHRs have increased for the Hang Seng Index (Hong Kong), FTSE STI (Singapore) and KLCI (Malaysia) implying higher hedging costs to the investors. Whereas, for the TAIEX (Taiwan) and SET 50 Index Thailand), the MVHRs have decreased and investors benefit from lower hedging costs. Besides, during the post-crisis period, the MVHRs have decreased for the Hang Seng Index and significantly increased for the FTSE STI, KLCI, TAIEX and SET 50 Index. Furthermore, all the four hedging techniques achieve significant risk reductions in the hedged portfolio compared to the unhedged position for all the five stock indices. Finally, although the performances of all hedging techniques did not vary significantly, it is certainly that the OLS perform slightly better than the other hedging techniques in improving the hedging effectiveness for all the five emerging futures market. Importantly, investors in the given markets should consider their level of risk aversion when hedging as the Bivariate-GARCH and the VECM performs well in-terms of returns.